Physiochemical Screening of Carica papaya Leaves with Specific Reference to Their Pharmacognostical Evaluation: Physiochemical Screening of Carica papaya Leaves with Specific Reference to Their Pharmacognostical Evaluation - Verma, Chhavi (International Journal of Pharmaceutical & Biological Archive, 2020)
Carica papaya is made to develop pharmacognostical characters of leaf with their morphological, microscopical, and physical characters including histochemical analysis. Morphological evaluation as color, odor, taste, size, shape, surface, and powder microscopy of plant shows the presence of endosperm cell which is polygonal in shape and contains aleurone grains and oil droplet, cell of testa, yellow coloring matter, and starch grains. Quantitative leaf microscopy to determine palisade ratio, stomata index, and vein-islet number is carried out. Peels are removed mechanically through epidermal peeling off and stomatal index (SI) is calculated. The vein-islet number, vein termination number, and palisade ratio of lamina are determined according to the standard method. We prepared the extracts of plant with different solvents for determining the different extractive values by maceration, Soxhlet extraction, successive extraction process, and determination of ash values, pH value, moisture content, and phytochemical screening to show the presence of carbohydrates, phenolic compounds, flavonoids, alkaloids, proteins, saponins, and lipids in the drug extract and fluorescence analysis in different solvent. Analysis of pesticide residues, aflatoxin, and heavy metals are also performed